2013
DOI: 10.1039/c3ee41817k
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light photocatalytic, solar thermal and photoelectrochemical properties of aluminium-reduced black titania

Abstract: Utilizing solar energy for hydrogen generation and water cleaning is a great challenge due to insufficient visible-light power conversion. Here we report a mass production approach to synthesize black titania by aluminium reduction. The obtained sample possesses a unique crystalline core-amorphous shell structure (TiO 2 @TiO 2Àx ). The black titania absorbs $65% of the total solar energy by improving visible and infrared absorption, superior to the recently reported ones ($30%) and pristine TiO 2 ($5%). The un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
502
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 650 publications
(519 citation statements)
references
References 42 publications
16
502
0
1
Order By: Relevance
“…Then, valence band spectra of TiO 2 -N and TiO 2−x -N were measured, and the valence band maximum (VBM) almost locates a similar value (1.99 eV below the Fermi energy, Figure 8b), consistent with the reported results [53]. Due to the same VBM, the above-mentioned decrease of E g value should be ascribed to the decrease of the conduction band minimum (CBM).…”
Section: Optoelectronic Propertiessupporting
confidence: 76%
“…Then, valence band spectra of TiO 2 -N and TiO 2−x -N were measured, and the valence band maximum (VBM) almost locates a similar value (1.99 eV below the Fermi energy, Figure 8b), consistent with the reported results [53]. Due to the same VBM, the above-mentioned decrease of E g value should be ascribed to the decrease of the conduction band minimum (CBM).…”
Section: Optoelectronic Propertiessupporting
confidence: 76%
“…Color change from white to black for TiO 2 nanomaterials reflects the change in optical properties and thus suggests the structural change after modification, at least the surface structural change. High-resolution transmission electron microscope (HRTEM) has revealed that a number of black TiO 2 nanomaterials have a crystalline/ amorphous core/shell structure, while white ones have clear lattice fringes throughout the crystals [22,23,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The amorphous or disordered surface layer has been considered the typical feature of black TiO 2 nanomaterials.…”
Section: Basic Properties Of Black Tio 2 Versusmentioning
confidence: 99%
“…It was proposed that improved photocatalytic performance of slightly hydrogenated TiO 2 could be attributed to the higher ratio of trapped holes (O − centers) and a lower recombination rate induced by the increase of surface defects, while the highly concentrated bulk defects in gray and black (overhydrogenated) TiO 2 acted as charge recombination centers, leading to worse photoactivity [57]. Huang's group has reported on the synthesis of a series of black TiO 2 nanomaterials by aluminum reduction [9,32,37,38,41,53]. The typical crystalline/amorphous core/shell structure was observed in almost all Al-reduced black TiO 2 [9,32,37,38,41], except for the black TiO 2 nanotubes [53].…”
Section: Black Tio 2 Nanomaterials As Visible Light-active Photocatalmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-doping with Ti 3 þ was further developed for narrowing the band of TiO 2 without the introduction of unwanted carrier recombination centres from dopants [19][20][21] , which consequently exhibited good stability and considerable activity for photocatalytic hydrogen production under visible light 20,21 . Recently, hydrogenation of crystalline TiO 2 was disclosed as a new approach to enhance the visible as well as infrared light absorption of pristine TiO 2 and subsequently triggered great interest [22][23][24][25][26][27][28] . The surface disorder of hydrogenated black TiO 2 , instead of bulk Ti 3 þ , was proposed to be responsible for the extended light absorption 23,24 .…”
mentioning
confidence: 99%